Endo-Perio Lesion and Uncontrolled Diabetes - Sara Dhoum; Kaoutar Laslami; Fatimazahraa Rouggani; Amal El Ouazzani; Mouna Jabri (Case Reports in Dentistry)
This work is to discuss the management of an endo-perio lesion, which represents a challenge to clinicians when it comes to diagnosis and prognosis of the involved teeth and especially with an altered general condition. A 50-year-old female patient with uncontrolled diabetes type 2 is suffering from a purulent discharge coming from the upper right canine. Endodontic and periodontal treatments were realized with 36 months radiological and clinical follow-up with the collaboration of her internist doctor.